Research progress of ARAIM technology - Ershen WANG; Di YANG; Chen HONG; Pingping QU; Xiaoyu LAN; Chuanyun WANG; Tao PANG (Dianxin kexue)
With the development of multi-constellation satellite navigation systems and dual-frequency technology,it has become possible to apply advanced receiver autonomous integrity monitoring(ARAIM) to higher-level vertical precision approaches.Firstly,three important contents related to ARAIM were introduced:integrity performance requirements,integrity support information,threat types and mitigation methods.Then,ARAIM related technologies research at home and abroad were summarized:fault classification,constellation configuration and ARAIM availability.Finally,combined with the current development of ARAIM,the future research was expected.